The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fagro.2021.730280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Narrow-Windrow Burning on Weed Dynamics in Soybean in Louisiana

Abstract: The soil seedbank allows for long-term persistence of weed species in agricultural fields. Some weed species can persist in the soil seedbank for extended periods. Restricting inputs into the weed seedbank has a large impact on future population density and influences management practices of these weeds in soybean production systems. Harvest weed seed control (HWSC) tactics incorporate mechanical and cultural management strategies to target weed seeds present at harvest. A 3-year trial was initiated to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This study showed promise that there is no yield penalty when implementing HWSC, and it is likely that it will contribute to preventing HR development (Beam et al 2019). Patterson et al (2021) reported that NWB alone was 62% more effective at reducing the Palmer amaranth seedbank compared to conventional harvest. In the same study, Palmer amaranth seedbank size increased from 40 to 100 seeds m −2 over 3 yr under a POST-only herbicide program.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study showed promise that there is no yield penalty when implementing HWSC, and it is likely that it will contribute to preventing HR development (Beam et al 2019). Patterson et al (2021) reported that NWB alone was 62% more effective at reducing the Palmer amaranth seedbank compared to conventional harvest. In the same study, Palmer amaranth seedbank size increased from 40 to 100 seeds m −2 over 3 yr under a POST-only herbicide program.…”
Section: Introductionmentioning
confidence: 82%
“…In the same study, Palmer amaranth seedbank size increased from 40 to 100 seeds m −2 over 3 yr under a POST-only herbicide program. In contrast, the use of NWB in addition to a POST-only herbicide treatment decreased seedbank density from an average of 42 to 18 seeds m −2 (Patterson et al 2021). The problematic status of Palmer amaranth as well as overall success under HWSC in soybean production demands alternative solutions such as NWB, and a determination of the temperature threshold necessary to reduce seed viability.…”
Section: Introductionmentioning
confidence: 99%